2013
DOI: 10.1007/s00234-013-1199-9
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation between pathology and neuromelanin MR imaging in Parkinson’s disease and dementia with Lewy bodies

Abstract: Based on the direct correlation between postportem NmMRI and neuropathological findings, signal intensity in the SNc is closely related to the quantity of neuromelanin-containing neurons but is not influenced by iron deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 17 publications
9
87
0
Order By: Relevance
“…NM containing structures can be identified in the NM-sensitive images (NM-MRI) as areas of hyperintensity. A direct comparison between post-mortem NM-MRI and neuropathological findings has shown that NM-MRI signal intensity in the SN is closely associated with the quantity of NM-containing neurons (Kitao et al, 2013), supporting the link between NM-MRI hyperintensity with the presence of NM.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…NM containing structures can be identified in the NM-sensitive images (NM-MRI) as areas of hyperintensity. A direct comparison between post-mortem NM-MRI and neuropathological findings has shown that NM-MRI signal intensity in the SN is closely associated with the quantity of NM-containing neurons (Kitao et al, 2013), supporting the link between NM-MRI hyperintensity with the presence of NM.…”
Section: Introductionmentioning
confidence: 96%
“…MRI techniques sensitive to NM (Sasaki et al, 2006; Kitao et al, 2013; Miyoshi et al, 2013; Ogisu et al, 2013; Ohtsuka et al, 2014) and iron (Graham et al, 2000; Martin et al, 2008; Baudrexel et al, 2010; Schweser et al, 2011; Lotfipour et al, 2012; Ulla et al, 2013) have been found to provide information about SN degeneration with potential applications as biomarkers of PD (Kashihara et al, 2011; Schwarz et al, 2011; Matsuura et al, 2013; Miyoshi et al, 2013; Castellanos et al, 2015). NM containing structures can be identified in the NM-sensitive images (NM-MRI) as areas of hyperintensity.…”
Section: Introductionmentioning
confidence: 99%
“…Part of our motivation for investigating the qMT properties of the SNc lay in seeking to understand the mechanism behind the hyperintensity of NM-containing structures in NM-MRI, a technique that has attracted interest as a potential means of quantifying neuronal loss in the SNc of patients with PD [16]. In particular, apart from the locus coeruleus, which also contains NM, both white matter and other grey matter structures of the brainstem, including the RN, appear hypointense relative to the SNc in NM-MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromelanin-sensitive MRI (NM-MRI) techniques [5] have shown notable contrast between the SNc and surrounding brain tissues, with a number of studies indicating that NM-MRI may be used to detect alterations to SNc morphology, even in early stages of PD [615]. Moreover, a direct comparison between post-mortem NM-MRI and neuropathology findings [16] found NM-MRI signal intensity in the SNc to be closely associated with the quantity of NM-containing neurons. However, the mechanism by which the presence of NM might give rise to signal hyperintensities on MRI, and the nature of the relationship between the loss of hyperintensity with advancing PD severity is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Using T1-weighted neuromelanin MR imaging, for example, a reduced signal intensity in the locus coeruleus was demonstrated in late PD patients [9]. Signal reduction directly correlated with the amout of neuromelanin-containing neurons in autopsied brains [10].…”
Section: Introductionmentioning
confidence: 98%